Design and Structure of an Electronic Switching System for Remote Circuits Structuring and Online Measurements - Larbaoui, Yassine; Naddami, Ahmed; Fahli, Ahmed (International Journal of Online and Biomedical Engineering (iJOE), 2022)
this paper presents design and structure of an electronic switching system for remote circuits structuring through internet, where the possibility of building circuits from scratch while conducting electrical measurements at any point of built circuits by online experimenters. This switching system enables to interconnect between electrical and electronic components in different combinations of circuits while providing an online environment highly approximated to physical environments of traditional hands-on laboratories in terms of manipulating measurement instruments and building experimental circuits. This paper also presents results of deployed topology for remote exploit of this switching system along with results of its deployed online engineering experiments.